Analisis Pembelajaran Pendidikan Agama Islam dengan Menggunakan Media Pembelajaraan Berbasis Card Toss di SMK Negeri 2 Tuban - Achoita, Ana; Kholifah , Fita; Rodhiyah, Isfa; Safitri, Yunni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The learning of Islamic Religious Education (PAI) in schools is often still dominated by the Teacher-Centered Learning (TCL) approach, which makes students less active and easily bored. This research aims to analyze the effectiveness of using the Card Toss learning media in improving the quality of PAI learning. The Card Toss method is a learning strategy that uses cards as interactive media to convey material, encouraging active student participation. This study uses a descriptive qualitative approach with data collection techniques through observation, tests, interviews, and documentation. The research subjects are tenth grade students at SMK Negeri 2 Tuban. The results of the study indicate that the implementation of the Card Toss method can enhance student learning engagement and the achievement of both basic competencies and competency achievement indicators. Evaluation was conducted through written and oral tests which showed an improvement in learning outcomes. This finding suggests that the Card Toss method can be an effective alternative in PAI learning and has the potential to be applied in other subjects across various levels of education